Nutritional Support in Acute Respiratory Distress Syndrome (ARDS): A Comprehensive Literature Review On Clinical Strategies and Patient Outcomes - Jakubowicz-Pawlak, Magdalena; Kuchenbeker, Natalia; Dojs, Adriana; Mierzwińska-Mucha, Julia; Siekaniec, Katarzyna (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Acute respiratory distress syndrome (ARDS) is a life-threatening condition and is a frequent reason for admitting patients to the Intensive Care Units. The treatment of ARDS remains an important task for physicians worldwide. Nutritional therapy is a significant part of managing critically ill patients. The aim of this study is to gather and present knowledge regarding nutrition support for patients diagnosed with ARDS. A brief description of the state of knowledge: Acute Respiratory Distress Syndrome (ARDS) is a severe inflammatory lung condition associated with high morbidity and mortality. While respiratory support remains the cornerstone of treatment, nutritional therapy has emerged as a critical component of care. Patients with ARDS experience increased metabolic demands and catabolism, necessitating individualized nutritional strategies to preserve muscle mass, support immune function, and improve clinical outcomes. Although enteral nutrition is preferred, parenteral routes are often required due to feeding intolerance or contraindications. Emerging evidence also supports the use of immune-modulating nutrients, such as omega-3 fatty acids and antioxidants, though clinical recommendations remain cautious pending further research. Refeeding syndrome remains a serious and potentially life-threatening complication necessitating careful monitoring and gradual reintroduction of nutrients. Conclusions: Nutritional support is a vital component in the management of ARDS, with significant implications for patient recovery and outcomes. Individualized strategies that address energy and protein needs, minimize the risk of refeeding syndrome, and consider both enteral and parenteral routes are essential. While immune-modulating nutrition holds promise, further high-quality studies are needed to establish its routine use. Integrating nutrition into ARDS care pathways may enhance treatment effectiveness and improve prognosis.